A brief overview on pitahaya (Hylocereus spp.) diseases - Valencia-Botín, Alberto J.; Kokubu, Hirotaka; Ruvalcaba Ruiz, Domingo (Journal of the Professional Association for Cactus Development, 2013)
The objective of this contribution is to present some recent advances in pitahaya (Hylocereus spp.) diseases research conducted in various parts of the world, thereby providing some information for promoting further studies on plant protection of the pitahaya species. Pitahaya is a cactus fruit crop of high demand at national and international level. It is cultivated in more than 10 countries worldwide. Prevalent form of cultivation until little more than 20 years was in small-scale family production. However, since its cultivation in commercial plantations and further domestication started in earnest, some symptoms of rotting and spots in stems and fruits were being observed. In some cases, commercial production plots had to be abandoned due to the diseases. In the decade of 1990s in Mexico, some studies on stem soft rot disease were initiated. It was found that at least two Enterobacteria were involved. With regard to the causing agent of the spots on stems, it was identified as fungus specie, Botryosphaeria dothidea Ces. & de Not, anamorph Fusicoccum sp. Morphological and physiological characterization were carried out in Mexico, to develop integrated management strategies. Anthracnose is yet another fungal disease that could become aggressive as it affects fruits and stems. Etiological studies in USA and Japan revealed the causing agent to be a fungus Colletotrichum gloesporioides Penz. Meanwhile, researchers in Taiwan described some morphological and genomic characteristics of a virus, Cactus Virus X. This virus causes a kind of mosaic on the stem, a mixture of light and dark green areas. Perspective of pitahaya as a commercial crop is promising. In terms of crop protection, however, it is necessary to determine genetic diversity of plant pathogen species as well as that of the causing agents and to develop integrated control measures. Moreover, few studies were made on the diseases in post-harvest. The viral disease is not yet to be reported in Mexico, but some personal observations appear to indicate that it is already present in commercial plantations in the country. It is thus imperative to initiate sampling, detection, and identification activities using traditional and molecular techniques. The final objective of all aforementioned aspects is to conserve and successfully manage pitahaya resource.